Boundary keeping and access to gaharu among Kenyah forest users - Wollenberg, Eva Karoline (2003)
As people living near forests in many parts of the world receive recognition of resource management rights, questions arise about where forest boundaries should be set and who should legitimately receive these rights. Drawing on research conducted among forest-dwelling Kenyah communities in Kalimantan, Indonesia, during 1995 to 1998, this paper shows that the realization of resource rights must be understood in the social context of how boundaries are interpreted and negotiated. Access to and control over forest resources is as much a matter of boundary keeping as of boundary setting. The analysis shows that boundary keepers assessed whether someone should be given access based on the potential user's entitlement, identity, and the potential for exchange. Understanding the 'fuzziness' of how seemingly clear boundary rules are applied should provide a more realistic picture of how groups gain and control access to resources in practice.